2010
DOI: 10.1007/s11631-010-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hydrogeochemical characteristics of groundwater in parts of the lower Benue Trough, Nigeria

Abstract: The aim of this work is to evaluate the hydrogeochemical characteristics of groundwater in parts of the lower Benue Through in Nigeria as well as to evaluate the variation in groundwater chemistry data and the suitability of the groundwater for drinking and other domestic purposes. This was based on chemical analyses of 44 water samples from existing wells and boreholes in the study area. From the statistical analysis (wide ranges, median and standard deviation), it is obvious that there are significant variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…According to Jalali (2007), the greatest threat to maintaining fresh water supply is depletion of the Uma and Onuoha 1991) resource that is used to fulfil the needs of the rapidly growing population. Studies by Edet and Ekpo (2008); Nganje et al (2010) and Edet and Okereke (2014) in parts of the present area of study showed that precipitation through rainfall, water-rock interaction, ion exchange and anthropogenic input are the main controlling factors to water composition.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…According to Jalali (2007), the greatest threat to maintaining fresh water supply is depletion of the Uma and Onuoha 1991) resource that is used to fulfil the needs of the rapidly growing population. Studies by Edet and Ekpo (2008); Nganje et al (2010) and Edet and Okereke (2014) in parts of the present area of study showed that precipitation through rainfall, water-rock interaction, ion exchange and anthropogenic input are the main controlling factors to water composition.…”
Section: Introductionmentioning
confidence: 57%
“…The Geochemical processes occurring within surface and groundwater and reactions with aquifer material have a great effect on water quality (Herczeg et al 1991), thus the evaluation of the importance of such processes is essential if the water resources are to be properly developed for human consumption, agricultural and industrial activities. The concentration of dissolved solute in water is controlled by several process such as weathering, dissolution and ion exchange (Panopaulos et al 2004;Kumar et al 2006;Garcia et al 2001;Singh et al 2005;Edet and Ekpo 2008;Nganje et al 2010). In the present work, various cross plot relations were used to evaluate the processes responsible for the variation in the chemistry of the water in the study area.…”
Section: Atmospheric Input and Water-rock Interactionmentioning
confidence: 99%
“…In respect of agricultural uses, groundwater from the different areas were put to be of low-salinity and low-alkalinity hazard, good to excellent quality for irrigation on the basis of Na%, sodium absorption ratio (SAR) and RSC. These studies were documented in the work of Longe et al (1987), Otezie (1991), Edet (1993), Olarewaju et al (1997), Udom et al (1998Udom et al ( , 2004, Edet et al (2011), Ajayi (1998), Ajayi and Obot (1998), Erah et al (2002), Ahiarakwem and Ejimadu (2002), Ogunbanjo (2004), Olobaniyi and Owoyemi (2004), Ozoko (2004), Adediji and Ajibade (2005), Ofoma et al (2005), Efe et al (2005), Edet and Okereke (2002), Alagbe (2006), Abulude et al (2007), Olobaniyi and Efe (2007), Adekunle et al (2007), Jatau and Bajeh (2007), Chukwu (2008), Boboye (2008), Adebo and Adetoyinbo (2009) and Nganje et al (2010).…”
Section: Introductionmentioning
confidence: 99%